Power Analysis Of Grand Vitara Car - Candiana, Cancan; , Ir. Tri Tjahjono, MT; , Ir. Subroto, MT (2014)
The objective of this research is to know the power engine of Grand Vitara Car.Research uses engine 2.0 liters. Use calculation analysis to know that power of Grand Vitara Car. The first step to start calculate we collects all the data engine of Grand Vitara Car, diameter of bore, length of stroke, volume of cylinder, and fuel used. After all the data has been collected. Then begins the process of calculation fuel decomposition, pressure, torque, and power. The calculation of the engine analysis of crank angle and pressure, that at crank angle 15o until 180o, the pressure table show is decreased, the engine analysis of crank angle and force, that at crank angle 15o until 180o, the force table show is decreased, the engine analysis of crank angle and torque, that at crank angle 15o until 30o, the torque show is increased, and at crank angle 45o until 180o, the torque show is decreased.